Early Response Assessment in Advanced Stage Melanoma Treated with Combination Ipilimumab/Nivolumab - Ma, Vincent T.; Chamila Perera, Alahendra A.; Sun, Yilun; Sitto, Merna; Waninger, Jessica J.; Warrier, Govind; Green, Michael D.; Fecher, Leslie A.; Lao, Christopher D. (Frontiers in Immunology, 2022)
Background: Standard combination ipilimumab/nivolumab (I/N) is given as 4 induction doses for advanced stage melanoma followed by nivolumab single-agent maintenance therapy. While many patients receive less than 4 doses due to immune-related toxicities, it is unclear if fewer doses of I/N may still provide long term clinical benefit. Our aim is to determine if response assessment after 1 or 2 doses of I/N can predict long-term survival and assess if fewer doses of I/N can lead to similar survival outcomes. Methods: We performed a retrospective analysis on a cohort of patients with advanced melanoma who were treated with standard I/N. Cox regression of progression-free survival (PFS) and overall survival (OS) models were performed to assess the relationship between response after 1 or 2 doses of I/N and risk of progression and/or death. Clinical benefit response (CBR) was assessed, defined as SD (stable disease) + PR (partial response) + CR (complete response) by imaging. Among patients who achieved a CBR after 1 or 2 doses of I/N, a multivariable Cox regression of survival was used to compare 1 or 2 vs 3 or 4 doses of I/N adjusted by known prognostic variables in advanced melanoma. Results: 199 patients were evaluated. Patients with CBR after 1 dose of I/N had improved PFS (HR: 0.16, 95% CI 0.08-0.33; p<0.001) and OS (HR: 0.12, 0.05-0.32; p<0.001) compared to progressive disease (PD). Patients with CBR (vs PD) after 2 doses of I/N also had improved PFS (HR: 0.09, 0.05-0.16; p<0.001) and OS (HR: 0.07, 0.03-0.14; p<0.001). There was no survival risk difference comparing 1 or 2 vs 3 or 4 doses of I/N for PFS (HR: 0.95, 0.37-2.48; p=0.921) and OS (HR: 1.04, 0.22-4.78; p=0.965). Conclusions: Early interval imaging with response during induction with I/N may be predictive of long-term survival in advanced stage melanoma. CBR after 1 or 2 doses of I/N is associated with favorable survival outcomes, even in the setting of fewer I/N doses received. Further studies are warranted to evaluate if electively administering fewer combination I/N doses despite tolerance in select patients may balance the benefits of therapy while decreasing toxicities.